STRATEGI MEDIA RELATIONS ITDC DALAM MEMBENTUK CITRA (STUDI PADA EVENT NUSA DUA FIESTA PERIODE 2014-2015) - Indira Sawitri, Cokorda Istri; Alit Suryawati, I Gusti Agung; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2017)
The purpose of this research is to describe or depict a media relations strategy undertaken by the PR ITDC seen through the Nusa Dua Fiesta event. This research is using qualitative method. The informants were selected by using purposive and snowball technique. The data were obtained through interviews, participation observation and documentation study. The technique of analyzing the data that used in this research trough several steps that was data reduction, data display, and conclusion drawing. The results of this research shows that media relations activities that have been done by ITDC are a press conference, a press reception, press calls, media briefings, and meetings with the media coordinator. Based on the six media relations strategies are used as indicators in this research, there are four media relations strategies implemented in the Nusa Dua Fiesta. Formally, the strategy is by serving the media, by supplying good copy, and by providing verifications facilities. In informal strategy is by building a personal relationship with the media. The strategy used by ITDC is a combination of informational and persuasive strategy strategy. Seen from routine PR spreading information through press releases, newsletters, held a gathering with the media, and held meetings with the media coordinator. In addition to doing publicity through print and electronic media, ITDC also spread through social media such as Facebook, and Instagram. Rated from public relations activities undertaken by ITDC appears that the newly formed image is the image of desire (wish image).   Keywords: ITDC, media relations, Nusa Dua Fiesta, strategy